Mentoring Khotmul Qur'an Santri Tpa Sholawat Ummi Through A Service-Learning Approach in Palangka Raya - Lutfi, Saiful; Norhidayah, Siti; Ningsih , Salsabila Hady; Surawan, Surawan (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
Khotmul Qur'an activity is an important activity as a sign that a santri has completed his learning. Therefore, this service was carried out with the aim of assisting Khotmul Qur'an Santri at TPA Sholawat Ummi to run solemnly through the service learning (SL) method with several stages carried out by the service team, namely 1) preparation and coordination. 2) opening of activities. 3) implementation of activities. 4) closing activities. The evaluation results prove that 1) preparation and coordination have been carried out in a planned and good manner, such as providing a comfortable and conducive place for the implementation of Khotmul Qur'an and various other preparations that have been well coordinated. 2) the opening of the activity is carried out by conveying the stages in carrying out Khotmul Qur'an activities and conveying advice to continue to be istiqomah in reading the Qur'an. 3) the implementation of activities has been carried out systematically in accordance with the stages that have been previously conveyed. 4) closing activities are carried out by reading prayers, distributing food and taking photos together to strengthen the relationship between students, ustadzah, and TPA Sholawat Ummi administrators.